2011
DOI: 10.1177/1090198110379580
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Health Education on Pap Smears in Peru

Abstract: Despite cervical cancer being one of the leading causes of cancer-related deaths among women in Peru, cervical Pap smear coverage is low. This article uses findings from 185 direct clinician observations in four cities of Peru (representing the capital and each of the three main geographic regions of the country) to assess missed opportunities for health education on Pap smears and other preventive women’s health behaviors during women’s visits to a health care provider. Various types of health establishments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Also, in Somalia women developed a negative outlook on screening due to embarrassment associated with female genital mutilation [15]. This could affect their decision to undergo Pap tests in the future [48]. Even though the age, level of education, occupational status and fear of Pap test result were significantly associated with ever Pap smear screening at bivariate analysis they were not significant at multivariate analysis.…”
Section: Consistent With Other Studies Factors Including Embarrassmementioning
confidence: 57%
“…Also, in Somalia women developed a negative outlook on screening due to embarrassment associated with female genital mutilation [15]. This could affect their decision to undergo Pap tests in the future [48]. Even though the age, level of education, occupational status and fear of Pap test result were significantly associated with ever Pap smear screening at bivariate analysis they were not significant at multivariate analysis.…”
Section: Consistent With Other Studies Factors Including Embarrassmementioning
confidence: 57%
“…Access to health care likely increases considerably for women with health insurance or residing in countries with universal health insurance, as Pap smear screening is one of many preventive health services offered under these coverage programs (25). In addition, health care providers may disseminate Pap smear knowledge and encourage screening, although a recent study of direct clinical observation in Peru found opportunities to educate patients on Pap smear screening were often missed by health care providers (26). …”
Section: Discussionmentioning
confidence: 99%
“…Providers can have a large influence on their patients’ health care decisions (28) and may be effective in addressing lack of knowledge and cultural barriers, particularly embarrassment, fear of pain, and the relationship between human papillomavirus (HPV) and cervical cancer. However, a recent study conducted in Peru found few health care providers take advantage of this opportunity (26). …”
Section: Discussionmentioning
confidence: 99%
“…Further, more than 90% are worried about the potential results (cancer) and pain associated with the procedure. Although simple, brief health education can help remedy this troubling response, few practitioners in Peru address this significant barrier to cancer prevention [13]. A culturally sensitive educational video can facilitate Pap test acceptance for both Quechua-and Spanishspeaking Peruvian women [4].…”
mentioning
confidence: 99%